Attitude of Health Care Providers on Snake Bite in Rural Community of Bangladesh - Ahsan, Hafez Mohammad Nazmul; Rahman, Md Ridwanur; Amin, Robed; Morshed, Syed Mahbub; Hossain, Md Amzad; Kamal, Mostafa (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Health care providers have different attitude and practice about the snake bite in rural community of Bangladesh. Objective: The purpose of the present study was to know the attitude and practice about the snake bite in rural community of Bangladesh. Methodolgoy: The findings from survey study on snake bite have been elicited from face to face interview with 243 number of medical professionals/health service providers consisting of 113 number of MBBS doctors, 86 number of nurses and 46 number of other health practitioners. The study area consisted of 5 zillasadar hospitals and 15 upazilla health complexes. This study aims to assess the Attitude and Practice of snakebite in rural community and effective management of snake bite through community engagement and using health care system of Bangladesh approach for prevention of snakebite in rural community and effective management of snake bite for the rural Bangladeshi people. It uses the methodological triangulation qualitative and quantitative approach as well as a case study design in analyzing data, whereby the exploratory-descriptive design is followed. Result: We purposively select the 243 sample (Doctors, Nurses, Paramedics ,Others) from the selected districts and its consisting random upazillas from the govt. sector hospitals keeping in mind gender balance (Male-Female) as a primary total target population. So in total, 5 division and its consisting random upazilas hospital including union health complex hospital personnel (From District, Upazilla& Community Hospitals)will be interviewed throughout mention areas of Bangladesh. The findings show that 60.1% of doctors, 50.0% of nurses and 56.8% of practitioners have a notion that the snake bite victims would go to Ozha followed by 11.5% of doctors, 4.7% of nurses and 11.4% of practitioners have a notion that they would go to the local healers and that of 26.5% of doctors, 41.9% of nurses and 32.9% of practitioners mentioned that the snake bite victims would go to doctors. The findings show that 69.0% of doctors, 64.0% of nurses and 56.8% of practitioners will recommend not to apply ‘ tight bandage’ to victim’s snake bite spot and 67.3% of doctors, 65.1% of nurses and 13.6% of practitioners will recommend not to apply ‘Suction by mouth or chick’ to victim’s snake bite spot. The findings show that 82.3% of doctors, 90.7% of nurses and 70.5% of practitioners applied first aid to the snake bite victim as their common practice. Conclusion: Majority of health professionals are well informed regarding harmful traditions and measures Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 28-32